(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
In the article, the historical stages of the origin, destruction and restoration of objects of the architectural and cultural landscape of the city of Baturyn, which urban development is associated with the activities of five Hetmans of Ukraine – Demian Ihnatovych (1669-1672), Ivan Samoilovych (1672-1687), Ivan Mazepa (1687-1708), Pylyp Orlyk (1710-1742) and Kyrylo Razumovsky (1750-1764) are considered. It is noted that the restoration and reconstruction of the architectural and cultural heritage of historical cities of Ukraine is one of the conditions for the preservation and regeneration of the historical memory of Ukrainians. The history of the urban development of Baturyn associated with the construction of the fortress and its citadel, around which the urban environment of the medieval city was formed, as well as its decline associated with the attack of the Moscow army, is studied. The period of revival of the Hetman’s capital is described, thanks to the state-building and economic activities of the last Hetman of Ukraine Kyrylo Razumovsky in 1750-1764. The history of the creation of the palace and park complex of K. Razumovsky by Charles Cameron and Antonio Rinaldi, its neglect and revival at the beginning of the 21st century simultaneously with other objects of the architectural and cultural landscape of today’s Baturyn is presented, namely: the citadel of the Baturyn fortress (1620); the estate of V.L. Kochubei with a park area located within the ancient Cossack park (late XVII – mid - XIX). K. Razumovsky (1799- 1803) with a parish school (1897). Okhor No. 883. The experience of successful implementation of the “Comprehensive Program for the Preservation of Monuments of the State Historical and Cultural Reserve “Hetman’s Capital” and the Development of Social and Engineering and Transport Infrastructure of Baturyn Village” at the expense of public-private partnership in the field of financing restoration and construction works is described.